PENGARUH PENGGUNAAN FILM CELLS AT WORK! (HATARAKU SAIBŌU) BERBASIS CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN MINAT BELAJAR SISWA PADA MATERI SISTEM IMUN KELAS XI MAN 1 JEMBER TAHUN AJARAN 2025/2026 - Silvi Faynani; Nanda Eska Anugrah Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of using the Cells at Work! film based on the Contextual Teaching and Learning (CTL) model on students’ conceptual understanding and learning interest in Grade XI students at MAN 1 Jember on the immune system topic. This study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group design. The sample consisted of an experimental class and a control class selected using the cluster random sampling technique. Data were collected through conceptual understanding tests (pretest and posttest), learning interest questionnaires, observation sheets, and documentation. The results showed that the use of the Cells at Work! film based on CTL had a significant effect on students’ conceptual understanding with a significance value of 0.001 (<0.05) and an experimental class posttest mean score of 97.91, which was higher than the control class score of 94.26. In addition, it significantly influenced students’ learning interest with a significance value of 0.000 (<0.05) and an average learning interest score of 88.34, higher than the control class score of 82.18. Therefore, the implementation of the Cells at Work! film based on CTL effectively improved students’ conceptual understanding and learning interest in the immune system topic.